Literature Study E-Commerce: Background, Methods Development System, Trend Topic, and Features - Erick Fernando; Yulius Denny Prabowo; Jullend Gatc (Journal of Applied Research In Computer Science and Information Systems, 2023)
This research focuses on conducting a literature review on e-commerce. With such extraordinary developments, users demand more functions and features. This has the impact of continuous development to attract more users to transact on e-commerce platforms. The research uses a systematic literature review approach with 30 appropriate and relevant articles in the 2017 - 2022 timeframe. Findings The findings of e-commerce development occurring at this time have different backgrounds. Transaction service systems and the absence of online marketing media are the most dominant backgrounds for e-commerce development. The topic of e-commerce development that has been widely developed is the sale of clothing, followed by development for SMEs. Many system development uses the waterfall method approach. In addition to discovering 27 features designed just for online shopping. These findings may serve as an example of how future developments in e-commerce might be improved to be more user-friendly and in tune with the requirements of the customer base.